Learning Through a Business Simulation Program among Semester 3 students of the Food Processing Technology Program (SPK) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2024)
The Food Enterprise course is a core course included in the curriculum content for the Food Processing Technology Program (SPK) which must be taken by Semester three (3) students. Through this course, students are required to carry out business activities or run a Business Simulation Program directly/hands-on. The objective of this study aims to assess students' understanding of the concept of management, which is the benefits that students have obtained through business simulation program activities. Besides that, also to identify the effect of the Business Simulation Program on students' soft skills. The study sample consisted of 159 student respondents of the third semester of the SPK Program which consisted of eight (8) Community Colleges which were Arau, Bagan Serai, Jelebu, Jerantut, Lahad Datu, Pasir Salak, Sabak Bernam and Sik. This study is with a quantitative design, which uses a questionnaire as a research instrument that is transferred in the form of a google form and distributed online to all respondents.  Data collected were analyzed with SPSS 21.0 statistical program. The results of the study analyzed in the form of frequency and percentage have shown that 98% of respondents agreed that the effects of business simulation programs can improve the understanding of financial management. In addition, this study also examines the benefits of business simulation programs for students. A total of 97% of respondents agreed that this business simulation program activities can benefit students to acquire social skills. In addition to that, this business simulation program should be continued because 97% of students agree that through this program students gain knowledge of business management. The results suggested that to improve the students in business abilities and simulations that mimic real business contexts with a certain degree of complexity and obstacles are necessary. Through this study it can also be used as a finding to help lecturers and the department in general in devising a more effective teaching and learning strategy as well as applying entrepreneurial elements along with the development of current technology to students. In conclusion, the business simulation program that has been implemented allows students to better understand aspects of business management that have been learned in theory.